Problem of diagnostics of deterioration in bone strength in children - A. L. Zyatitskaya (Бюллетень сибирской медицины)
The most part of the bone mass is formed between 10 and 14 years. The age of achievement of the peak bone mass in different parts of skeleton varies from 17 to 30 years. Low values of the peak bone mass are a significant risk factor, since the formed bone substance is expended later. Measures aimed at the early diagnostics, revealing of risk groups, and prophylaxis of reduction of the bone strength in children will favor the gain in health of children population and in the life quality in both children and adult people and will provide the economy of material resources.